Next generation sequencing identifies mutations in Atonal homolog 7 (ATOH7) in families with global eye developmental defects - ELÇİOĞLU, HURİYE NURSEL; ŞAHİN, ÖZLEM (OXFORD UNIV PRESS, 2012)
The atonal homolog 7 (ATOH7) gene encodes a transcription factor involved in determining the fate of retinal progenitor cells and is particularly required for optic nerve and ganglion cell development. Using a combination of autozygosity mapping and next generation sequencing, we have identified homozygous mutations in this gene, p.E49V and p.P18RfsX69, in two consanguineous families diagnosed with multiple ocular developmental defects, including severe vitreoretinal dysplasia, optic nerve hypoplasia, persistent fetal vasculature, microphthalmia, congenital cataracts, microcornea, corneal opacity and nystagmus. Most of these clinical features overlap with defects in the Norrin/beta-catenin signalling pathway that is characterized by dysgenesis of the retinal and hyaloid vasculature. Our findings document Mendelian mutations within ATOH7 and imply a role for this molecule in the development of structures at the front as well as the back of the eye. This work also provides further insights into the function of ATOH7, especially its importance in retinal vascular development and hyaloid regression.
Keywords: RETINAL GANGLION-CELL; GENOME-WIDE ASSOCIATION; OPEN-ANGLE GLAUCOMA; EXUDATIVE VITREORETINOPATHY; OPTIC-NERVE; NORRIE-DISEASE; FATE DETERMINATION; ATONAL HOMOLOG; FZD4 MUTATIONS; VASCULATURE